Rheumatoid Arthritis and Oxidative Stress: Rheumatoid arthritis and OA - Zamudio-Cuevas, Yessica; Martínez-Flores, Karina; Martínez-Nava, Gabriela Angélica; Clavijo-Cornejo, Denise; Fernández-Torres, Javier; Sánchez-Sánchez, Roberto (Cellular and Molecular Biology, 2022)
Rheumatoid arthritis (RA) is an autoimmune disease that affects approximately 1% of the worldwide population. In recent decades, oxidative stress (OS) has been shown to be involved in the progression of this disease through DNA, lipid and protein damage, resulting in synovial inflammation. There are many causes of OS; metabolism is involved in the production of reactive oxygen species (ROS) but pollution, diet and microbiota imbalances could lead to the overproduction of these ROS. A decade of research focused on understanding how OS is promoted by known RA risk factors is described herein. The use of antioxidants represents an integrative treatment for patients with rheumatoid arthritis, given the evidence of the damage caused by oxidative stress in this disease. Understanding the different factors that contribute to the development and progression of RA, such as OS, will pave the way not only for better pharmacological treatments but also for recommendations for dietary and health behaviours that will benefit patients with this disease.